Transformasi Tradisi Osongkapali di Kenagarian Sungai Patai Tahun 1994-2023 - Afrolanda Afrolanda; Siti Fatimah (Journal on Education, 2023)
The Osongkapali tradition is a hereditary tradition carried out by the Kenagarian Sungai Patai indigenous people, Sungayang District, Tanah Datar Regency. The Osongkapali tradition is one of the unique burial processes of the princes in West Sumatra. Osongkapali is a coffin used to carry the body of the prince when the prince dies. The purpose of this study was to (1) find out the procession for holding the funeral of the prince's remains at Kenagarain Sungai Patai, Sungayang District, Tanah Datar Regency, West Sumatra in 1994-2023. (2) To find out the transformation of the funeral procession for the leader's funeral at Kenagarain Sungai Patai, Sungayang District, Tanah Datar Regency, West Sumatra in 1994-2023. This study uses historical research methods. First, heuristics (data collection), primary or secondary data. Second, source criticism, internal and external criticism. The third interpretation is understanding the source under study. Fourth, historiography (writing of research results). The results of this study indicate that in the Osongkapali tradition there are transformations including transformations in